'Use of antipsychotics in children and adolescents: a picture from the ARITMO population-based European cohort study'. (20th April 2020) - Kaguelidou, Florentia; Holstiege, Jakob; Schink, Tania; Bezemer, Irene; Poluzzi, Elisabetta; Mazzaglia, Giampiero; Pedersen, Lars; Sturkenboom, Miriam; Trifirò, Gianluca
Abstract: Aims: Prevalence of the use of antipsychotics (APs) in the paediatric population is globally increasing. The aim of this study was to describe multinational trends and patterns in AP use in children and adolescents in Europe. Methods: This was a dynamic retrospective cohort study comprising all children and adolescents (⩽18 years of age). Data were extracted from five population-based electronic healthcare databases in Europe (Denmark, Germany, Italy, the Netherlands and United Kingdom) from 2000 to 2010. Yearly prevalence and incidence of AP use was expressed per 1000 person-years (PYs). Results: Prevalence increased from 1.44 to 3.41/1000 PYs (2008) in Denmark and from 2.07 to 4.35/1000 PYs in the NL (2009), moderately increased from 2.8 to 3.24/1000 in UK (2009) and from 1.53 to 1.74/1000 PYs in Germany (2008) and remained low from 0.61 to 0.34/1000 PYs in Italy (2010). Similarly, incidence rates increased from 0.69 to 1.52/1000 PYs in Denmark and from 0.86 to 1.49/1000 PYs in the NL, stabilised from 2.29 to 2.37/1000 PYs in the UK and from 0.79 to 0.80/1000 PYs in Germany and remained low from 0.32 to 0.2/1000 PYs in Italy. AP use was highest in 15–18 year olds and in boys compared to girls. Yet, the use observed in the 5–9 year olds was found to be comparatively high in the NL. Prescriptions of second generation APs, especially risperidone, were privileged but the first generation APs were still prescribed in the youngest. Conclusions: A steady increase in AP use in children and adolescents was observed essentially in the NL and Denmark. The use in Germany and Italy was lowest among countries. The use of APs under 9 years of age underlines their off-label use and should be carefully monitored as the risk/benefit ratio of these medications remains unclear in young children. AP use was altogether lower in Europe as compared to that reported in North America.